2001
DOI: 10.1016/s1010-7940(01)00647-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe obesity does not adversely affect perioperative mortality and morbidity in coronary artery bypass surgery

Abstract: Objective: Obese patients are usually thought to have an increased risk for complications in coronary artery bypass surgery. Methods: Therefore, the data of 500 consecutive patients undergoing coronary artery bypass grafting at our department in 1998 by use of cardiopulmonary bypass were analyzed. Severe obesity was de®ned as body mass index (BMI) $ 30:0 kg/m 2 . Obese patients (n 100; group O) were compared to the remaining 400 patients (group C). Both groups were comparable with respect to sex, history of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
3
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 10 publications
5
70
3
2
Order By: Relevance
“…20 In cases of MI and coronary angioplasty, patients with obesity had better survival and similar rates of cardiac events as compared to patients with normal weight, and these results are very comparable to ours.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…20 In cases of MI and coronary angioplasty, patients with obesity had better survival and similar rates of cardiac events as compared to patients with normal weight, and these results are very comparable to ours.…”
Section: Discussionsupporting
confidence: 85%
“…14 -20 In particular, increased BMI was independently associated with better outcome in patients with MI, 14 heart failure, [15][16][17] renal dialysis, 18 percutaneous transluminal coronary angioplasty, 19 and coronary artery bypass surgery. 20 In a recent national U.S. survey of a noninstitutionalized population, among stroke survivors a higher BMI was associated with increased mortality in younger individuals and declined linearly with increasing age. 21 However, there are no data for the relation between obesity and survival in patients who have experienced an acute stroke.…”
mentioning
confidence: 99%
“…The link may be related to the procoagulant state seen in metabolic syndrome and obesity, which is characterized by higher levels of tissue factor and Factor VIII, fibrinogen, inhibition of fibrinolytic pathways (decreased tissue plasminogen activator activity and increased plasminogen activator inhibitor-1), and greater PLT aggregability due to the presence of hyperlipidemia and endothelial dysfunction that is frequently encountered in obese patients. 20,22) Considering the varying risks of adverse outcomes for different BMI groups, it is clear that ours was not the first study to contradict the prevailing view that obesity is a risk factor for operative mortality and morbidity following CABG 23) or to infer that obesity may protect against some adverse outcomes. 24) Several previous studies have suggested that underweight is related to low cardiac output syndrome, strokes, bleeding, and prolonged ventilator therapy.…”
Section: Discussionmentioning
confidence: 77%
“…Obesity may have been an important factor that may have contributed to the observed host defense impairments in the leptin-deficient mice. However, this seems unlikely because obesity was not a significant risk factor for nosocomial pneumonia in human patients (43)(44)(45). Of the abnormalities associated with the leptin-deficient mice, excess glucocorticoid synthesis might have the most potent immune suppressive effects.…”
Section: Discussionmentioning
confidence: 99%